Neurons show distinctive DNA methylation profile and higher interindividual variations compared with non-neurons - Iwamoto, Kazuya; Bundo, Miki; Ueda, Junko; Oldham, Michael C.; Ukai, Wataru; Hashimoto, Eri; Saito, Toshikazu; Geschwind, Daniel H.; Kato, Tadafumi (Genome Research, 2011)
Epigenome information in mammalian brain cells reflects their developmental history, neuronal activity, and environmental exposures. Studying the epigenetic modifications present in neuronal cells is critical to a more complete understanding of the role of the genome in brain functions. We performed comprehensive DNA methylation analysis in neuronal and non-neuronal nuclei obtained from the human prefrontal cortex. Neuronal nuclei manifest qualitatively and quantitatively distinctive DNA methylation patterns, including relative global hypomethylation, differential enrichment of transcription-factor binding sites, and higher methylation of genes expressed in astrocytes. Non-neuronal nuclei showed indistinguishable DNA methylation patterns from bulk cortex and higher methylation of synaptic transmission-related genes compared with neuronal nuclei. We also found higher variation in DNA methylation in neuronal nuclei, suggesting that neuronal cells have more potential ability to change their epigenetic status in response to developmental and environmental conditions compared with non-neuronal cells in the central nervous system.